Paul Erdős's mathematics as a social activity. Issue 2 (4th May 2019) - Rekvenyi, Kamilla
Abstract : This essay, which won the 2018 BSHM undergraduate essay prize, investigates the collaborative mathematical practice of Paul Erdős. It draws on new unpublished primary sources and oral history in both English and Hungarian. It raises the question of whether communal mathematics, or mathematics as a social activity, can lead to individual success.